Diversity in family life course patterns and intra-cohort wealth disparities in late working age - Nicole Kapelle; Sergi Vidal (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
Against the backdrop of soaring wealth inequalities in older age, this research addresses the relationship between increasingly diverse family life courses and widening wealth differences between individuals as they age. We holistically examined how childbearing and marital histories matter for West German baby boomer cohorts' personal wealth at ages 51 to 59. We proposed that wealth penalties associated with departures from culturally and institutionally supported family patterns accumulate overtime and can explain wealth inequalities at older ages. We tested our thesis using longitudinal data from the German Socio-Economic Panel Study (SOEP, v34, waves 2002-2017). We first identified typical family trajectory patterns between ages 16 and 50 using multichannel sequence analysis and cluster analysis. We then modeled personal wealth ranks at ages 51 to 59 as a function of family patterns. Results showed that departures from a standard family pattern consisting of a stable marriage with (on average, two) children was associated with lower wealth ranks at older age. We also found higher wealth penalties for greater deviation and lower penalties for moderate deviation from the standard family pattern. Addressing entire family trajectories, our research extended and nuanced our knowledge of the role of earlier family behavior for later economic wellbeing. By using personal-level wealth data instead of household-level data, we were able to identify substantial gender differences in the study associations. Our research also recognizes the importance of combining marital and childbearing histories to assess the relationship between family life courses and wealth inequality.
Keywords: 330; Family; Life Course; Inequality/Social Stratification